Importancia de la auditoría forense como instrumento de control de la fiscalización tributaria en la detección de la evasión fiscal del impuesto de industria, comercio y avisos en el municipio de Santa Lucia (2014)
The objective of the research is to determine the importance of forensic audit as an instrument of control tax examination in detecting tax evasion Industry, Trade and Jobs in Santa Lucia Atlantic. To this end, a quantitative descriptive study whose scope was the deductive method was structured; design used was non-experimental, cross-correlation and causal Likert survey was established applied to officials of the Ministry of Finance. The results show that the agents involved in the control of the municipality are aware of the characteristics of tax evasion and the minimum requirements that must hold this process to minimize their occurrence; however, this service displays of public finances needs a number of administrative and procedural nature which constitute the cause of the presence of this financial fraud; in this situation, the sample said that the forensic audit stands as an efficient instrument to strengthen controls and implement them in the absence of. It is concluded that the forensic audit is a tool for the institutions responsible for the management of taxes, with which you can obtain proof and evidence about the consummation of this type of financial fraud that causes so much damage to society.